61.2k views
0 votes
Solve: n^2/2 -2 = 5n/6

User JohnnyHK
by
5.3k points

1 Answer

6 votes

Answer:

n = -4/3 or n = 3

Explanation:

Multiply by 6 to eliminate fractions, then put into standard form.

3n^2 -5n -12 = 0

3n^2 -9n +4n -12 = 0 . . . . . separate -5n into two terms to facilitate factoring

3n(n -3) +4(n -3) = 0 . . . . . factor pairs of terms

(3n +4)(n -3) = 0 . . . . . . . . . factor out the common factor

n = -4/3 or 3 . . . . . . . values that make the factors be zero

Solve: n^2/2 -2 = 5n/6-example-1
User SyAu
by
5.4k points